Badanie satysfakcji pracowników w przedsiębiorstwach przemysłu spożywczego - Pietroń-Pyszczek, Agata (Employees' Satisfaction Research in Food Industry Companies, 2005)
The article concerns a legitimate problem of carrying out the regular research on the employees' satisfaction. The potential diagnostic instruments and problems connected with their utilization are also presented. Theoretical considerations are confronted with the results of survey performed in 16 enterprises. In most cases it appears that managerial staff does not utilize proper solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 187-191